PEMBASMI HAMA SERANGGA MENGGUNAKAN CAHAYA LAMPU BERTENAGA SOLAR CELL - Subandi - (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
In the general area of ​​rice fields found many kinds of insects that destroy rice plants. One of the properties of insects is to have an interest in light, in practice traditionally it has long been applied for example using a lamp pumped to catch insects (moths). The light intensity can affect insect behavior (hamma) that can be used in agriculture (hamma control insects) and can be used as animal feed. The problems are very interesting to be experiments in this study was designed prototype insect repellent uses light solar powered lamp that is safe from a short circuit and a fire. The working principle of this prototype is when the sun sank in the afternoon, the lights light trap will turn on automatically for electrical energy emitted comes from batteries, solar panels will convert solar energy into electrical energy and then store it in the battery, then converted electric unidirectional (dc) into alternating electric current (ac) using the inverter to flow into the trap light lamps (TL ultraviolet). Prototype testing was conducted for 4 hours/day from 18:00 until 22:00pm, at these times most insect activity comes closer to an ultraviolet lamp. In accordance with the magnitude of the solar panel and the battery used in this prototype, the electrical load that can be supplied to the 10 watt UV lamp (6 hours/day), 15watts (4 hours/day), 20watts (3 hours/day). Ultraviolet light 20watt lamp is able to collect insects in large numbers consisting of hamma leafhoppers, beetles, walang rice pest, crickets, and grasshoppers. Indirectly, this prototype could be said to be very helpful to farmers in terms of overcoming hamma attacks on rice